2011
DOI: 10.1097/shk.0b013e3181f6aab0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 1 Mediates Acetylation and Release of High Mobility Group Box 1 from Hepatocytes During Murine Liver Ischemia-Reperfusion Injury

Abstract: Damage-associated molecular patterns (DAMPs) initiate inflammatory pathways that are common to both sterile and infectious processes. The DAMP, high-mobility group box 1 (HMGB1), and the transcription factor, interferon regulatory factor 1 (IRF-1), have been independently associated as key players in ischemia-reperfusion (I/R) injury. Our study demonstrates that IRF-1 contributes to hepatocellular release of HMGB1 and further that IRF-1 is a necessary component of HMGB1 release in response to hypoxia or after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 41 publications
1
69
1
Order By: Relevance
“…[10][11][12] Interestingly, HMGB1 was reported to rapidly mobilize and release into system circulation from damaged liver in the setting of liver I/R injury. 34,35 Previous studies also demonstrated that serum HMGB1 level remained elevated until 12 h after reperfusion, and that the removal of excessive serum HMGB1 with adsorption column improved the lung injury score. 28 Whether or not HMGB1 was transported to the lung and whether downstream signaling pathways in lung were activated was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Interestingly, HMGB1 was reported to rapidly mobilize and release into system circulation from damaged liver in the setting of liver I/R injury. 34,35 Previous studies also demonstrated that serum HMGB1 level remained elevated until 12 h after reperfusion, and that the removal of excessive serum HMGB1 with adsorption column improved the lung injury score. 28 Whether or not HMGB1 was transported to the lung and whether downstream signaling pathways in lung were activated was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this study did not examine the role of HAT enzymes in hepatic I/R, recent findings from our laboratory suggest that HAT activation during I/R also contributes to HMGB1 acetylation (45). Our ongoing investigations are focused on understanding the balance between both HAT and HDAC activities in the mobilization and release of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…266 Notably, during hepatic I/R injury-induced liver damage, the nuclear upregulation of IRF1 has been linked to the expression of functional TLR4. 267 However, whether and how other molecular signaling pathways are involved in IRFrelated I/R injury require further investigation.…”
Section: Upstream Irf Signaling In I/r Injurymentioning
confidence: 99%